The powdery mildew effector Eae1 targets a SAMS enzyme within the ethylene biosynthesis pathway to disrupt plant immunity - Jiaxin Shan; Fan Su; Jinyao Yin; Yuhan Liu; Xuehuan Zhu; Minghao Zuo; Wenbo Liu; Chunhua Lin; Xiao Li; Weiguo Miao (Phytopathology Research)
Abstract Phytopathogens secrete effector proteins that disrupt plant immunity. Phytohormones, such as ethylene, function as immune signals that regulate plant responses to phytopathogens. However, the mechanisms by which powdery mildew fungi utilize effectors to manipulate ethylene signaling remain poorly understood. This study reports that Eae1, an effector from the powdery mildew fungus Erysiphe quercicola, can reduce ethylene levels and attenuate the immune response in rubber trees (Hevea brasiliensis), thereby promoting fungus infection. Notably, Eae1 shares homologs with effectors from other powdery mildew fungi. Our findings indicate that the Eae1 transcription can be induced by enhanced ethylene signaling. Eae1 is translocated to plant chloroplasts, where it destabilizes Hevea brasiliensis S-adenosyl-L-methionine synthetase, a key enzyme in ethylene biosynthesis, leading to reduced ethylene production. The chloroplast-localized protein Toc159/AIG1 (AIG1) may facilitate this interaction. Overall, our study reveals a mechanism by which powdery mildew fungi disrupt ethylene-mediated resistance in host plants.